The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1074/jbc.271.46.28749
|View full text |Cite
|
Sign up to set email alerts
|

Converting Tissue-type Plasminogen Activator into a Zymogen

Abstract: In striking contrast to most other members of the chymotrypsin family of serine proteases, tissue-type plasminogen activator (t-PA) is not synthesized and secreted as a true zymogen. The zymogenicity, or ratio of the catalytic efficiencies of the mature, two-chain enzyme and the single-chain precursor, is only 5-10 for t-PA. This exceptional property of t-PA, however, is not shared by urokinase (u-PA), a plasminogen activator that is very closely related to t-PA. The molecular basis of this important functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 58 publications
2
25
1
Order By: Relevance
“…We demonstrated that the absence of the zymogen triad contributes to the enzymatic activity of single-chain t-PA (8,9), and two groups have suggested that Lys 156 2 stabilizes an active conformation of single-chain t-PA (11,12). Consistent with the latter suggestion, we have demonstrated that conversion of His 144 of t-PA to an acidic residue, which we predicted would alter the conformation of Lys 156 , selectively suppressed the catalytic activity of single-chain t-PA (10).…”
supporting
confidence: 75%
“…We demonstrated that the absence of the zymogen triad contributes to the enzymatic activity of single-chain t-PA (8,9), and two groups have suggested that Lys 156 2 stabilizes an active conformation of single-chain t-PA (11,12). Consistent with the latter suggestion, we have demonstrated that conversion of His 144 of t-PA to an acidic residue, which we predicted would alter the conformation of Lys 156 , selectively suppressed the catalytic activity of single-chain t-PA (10).…”
supporting
confidence: 75%
“…This equilibrium lies far to the left when the proteins are unactivated and typically lies far to the right following activation. Notable exceptions are tissue type plasminogen activator, which has significant activity as a zymogen (low zymogenicity), and factor VIIa, which fails to attain its catalytically competent conformation after cleavage of the Arg 15 -Ile 16 bond (high zymogenicity) (53,54). For trypsin and FXa, the zymogen-like conformation is negligibly populated.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of Enzymes by Transient Transfection of COS Cells-cDNAs encoding t-PA; t-PA/R15E; t-PA/Q192E; t-PA/Q192M; t-PA/R15E,Q192E; and t-PA/R15E,Q192M were ligated into the transient expression vector pSVT7 (28) and then introduced into COS cells by electroporation using a Bio-Rad gene pulser as described previously (29,30). 20 g of cDNA, 100 g of carrier DNA, and approximately 10 7 COS cells were placed into a 0.4-cm cuvette, and electroporation was performed at 320 V, 960 microfarads, and ohm ϭ ϱ.…”
Section: Site-directed Mutagenesis and Construction Of Expression Vecmentioning
confidence: 99%